PENGARUH STRUKTUR KEPEMILIKAN SAHAM, KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Yang Terdaftar di BEI) - Herni Ali; Miftahurrohman Miftahurrohman (ETIKONOMI, 2014)
The main objective of this study is to examine the impact of ownership structure, dividend policy, debt policy on the value of the firms in Indonesian Stock Exchange. Data used in this research is financial data in the form  financial statements of public companies listed in Indonesian Stock Exchange. The statistical method used to test the hypothesis is Structural Equation Modeling (SEM) analysis. The results of this study  shown that: ownership structure has a significant positive influence to dividend policy. Ownership structure significant negative influence to debt policy. Ownership structure have no influence to value of the firms. Dividend policy significant negative influence to debt policy. Dividend policy have no influence to value of the firms. Debt policy significant positive influence to value of the firms.DOI: 10.15408/etk.v13i2.1883